TEACHING LISTENING TO NARRATIVE TEXT VIA YOUTUBE AUDIO-VIDEO TO CLASS X STUDENTS OF SMAN 6 ABDYA - Suwirda, Suwirda; Zuhri Efendi (Nusantara Hasana Journal, 2025)
This study aims to examine the effectiveness of using YouTube-based narrative videos in improving the listening skills of the narrative text of class X students of SMAN 6 Aceh Barat Daya. The research method employed a descriptive quantitative approach with a quasi-experimental design, including a pre-test and post-test control group design. The research sample consisted of two purposively selected classes, namely class X.1 as the experimental group (n = 36) taught using YouTube narrative video media, and class X.3 as the control group (n = 34) taught using conventional audio-based methods. The research instrument was a multiple-choice test covering four aspects of listening skills: main idea, detailed information, inference, and vocabulary in context. Data analysis used an independent sample t-test through SPSS version 26 with a significance level of 0.05. The results showed a significant difference between the post-test scores of the two groups (p = 0.000), where the experimental group experienced an average increase of 23.5 points, higher than the control group, which increased by 8.7 points. In addition, improvements occurred in all listening sub-skills, with the highest percentage in understanding the main idea (28%). The findings indicate that the use of YouTube narrative videos is more effective than conventional methods in improving students' listening skills, while increasing their motivation and engagement in learning.